Neonatal state and degree of necessity for parental care in Maiasaura based on inferred neonatal metabolic rates - Hugo Bert; Holly Woodward; Nicolas Rinder; Romain Amiot; John R. Horner; Christophe Lécuyer; Mariana Sena; Jorge Cubo (Scientific Reports)
Abstract We infer the neonatal metabolic rate at rest (RMR) and at maximum activity levels (MMR) of the hadrosaurid dinosaur Maiasaura peeblesorum from the Two Medicine Formation of Montana (USA) using Phylogenetic Eigenvector Maps applied to the following osteohistological features: the Relative Primary Osteon Area and the size of the femoral nutrient foramen as proxies. We investigate the locomotor/motor activity of the neonates by comparing the difference between maximum and minimum rates of oxygen consumption—referred to as aerobic scope and denoted as ΔMR, as a proxy of their activity levels. Applied to Maiasaura, this novel methodology allows for a quantitative assessment of its neonatal state and to deduce its dependence on parental care. The inferred neonatal RMR values for Maiasaura are similar to those of present-day fast-growing endotherms. As for the aerobic scope, M. peeblesorum neonates have a ΔMR value similar to those observed in present-day altricial birds that need intensive parental care. This result is consistent with the previously proposed hypothesis of nidicolous M. peeblesorum requiring parental care. Finally, based on age-estimations from M. peeblesorum neonate remains found both in and outside nest sites, we estimate that this species remained in the nest for approximately 40–75 days. Maiasaura provides a useful ecological baseline from which to infer neonatal states in an other hadrosaur of similar adult size—Hypacrosaurus stebingeri, whose differing ecological traits point to a relatively more precocial condition. The diversity of post-hatching reproductive strategy partly explains the adaptation of hadrosaurs to a wide range of paleolatitudes and environments.